The evolution of social wasps - Hunt, James H. (Oxford University Press, 2007)
'The Evolution of Social Wasps' resolves one of evolution's most intriguing problems - the origin of insect sociality. It also challenges conceptual approaches that have dominated three decades of social behaviour research.